From COVID-19 to Resilience: Quantitative Methods in Economics and Business - Novickytė, Lina; Droždz, Jolanta; Pastusiak, Radosław; Soliwoda, Michał (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The present reprint contains 11 articles accepted for publication and published in the Special Issue From COVID-19 to Resilience: Quantitative Methods in Economics and Business of the MDPI Mathematics journal. These articles cover a wide range of topics analyzing economics and business situations during and post the COVID-19 pandemic. It is hoped that these selected research papers will be found to be impactful by the international scientific community and that these papers will facilitate further research on quantitative techniques for solving complex problems in various disciplines and application fields.